2002
DOI: 10.1038/416613a
|View full text |Cite
|
Sign up to set email alerts
|

Optical studies of solid hydrogen to 320 GPa and evidence for black hydrogen

Abstract: The quest for metallic hydrogen at high pressures represents a longstanding problem in condensed matter physics. Recent calculations have predicted that solid hydrogen should become a molecular metal at pressures above 300 GPa, before transforming into an alkali metal; but the strong quantum nature of the problem makes the predictions difficult. Over a decade ago, an optical study of hydrogen was made using a diamond anvil cell to reach 250 GPa. However, despite many subsequent efforts, quantitative studies at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
313
4
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(344 citation statements)
references
References 23 publications
21
313
4
2
Order By: Relevance
“…Indeed, quantum ion motion usually favours phases with lower ion-ion correlations, which would further stabilize the low-temperature liquid phase found here. In addition, our findings are consistent with pressure estimates from experiments where hydrogen is expected to metallize 3, 29 . Finally, we note that the observed increase in MLWF spreads when going from the high-pressure solid to the molecular liquid phase points at the presence of dynamically-induced intermolecular charge transfer (dipole moments); this indicates that the transition from solid to liquid at high pressure is accompanied by an increase of the hydrogen infrared absorption.…”
supporting
confidence: 81%
“…Indeed, quantum ion motion usually favours phases with lower ion-ion correlations, which would further stabilize the low-temperature liquid phase found here. In addition, our findings are consistent with pressure estimates from experiments where hydrogen is expected to metallize 3, 29 . Finally, we note that the observed increase in MLWF spreads when going from the high-pressure solid to the molecular liquid phase points at the presence of dynamically-induced intermolecular charge transfer (dipole moments); this indicates that the transition from solid to liquid at high pressure is accompanied by an increase of the hydrogen infrared absorption.…”
supporting
confidence: 81%
“…5 that at 400 GPa on our scale, the old MXB86 scale would give a pressure 67 GPa lower, or 333 GPa. Perhaps this explains the conflict between Narayana et al 11 and Loubeyre et al 12 on hydrogen at high pressures.…”
Section: The Calibrationmentioning
confidence: 89%
“…Narayana et al 11 studied hydrogen in a DAC to 342 GPa and observed that the sample remained transparent to this pressure ͑the only measurement made on the sample was this visual one͒. Later, Loubeyre et al 12 studied hydrogen and observed it to become black at a lower pressure, 320 GPa. Two possible solutions to these contradictory results are that Narayana et al did not have a sample in their DAC gasket, but they are confident that they did, 13 and that the pressure scales were incorrect so that the sample of Loubeyre et al was really at a higher pressure than that of Narayana et al Narayana et al used the x-ray-marker method and determined the pressure from that of the gasket adjacent to the sample, making a correction to the pressure in the gasket because it was not embedded in the hydrogen sample.…”
Section: Introductionmentioning
confidence: 99%
“…Our study leads to a radical revision of the DFT phase diagram of hydrogen up to nearly 400 GPa. That the most stable phases remain insulating to very high pressures eliminates a major discrepancy between theory 5 and experiment 6 . One of our new phases is calculated to be stable over a wide range of pressures, and its vibrational properties agree with the available experimental data for phase III.…”
mentioning
confidence: 99%